The hard-pressed researcher a research handbook for the caring professions - Edwards, Anne (Pearson, 1999)
The Hard-pressed Researcher provides practical guidance on how to undertake a research project. It provides step-by-step guidance from conceptualisation through to report writing. Each chapter provides sources for further reading and the book ends with a series of statistical tables.